Histopathological patterns of ovarian tumors at BPKIHS - Pradhan, A; Sinha, A K; Upreti, D (Health Renaissance, 2012)
Introduction: Ovarian tumors account for fifth most common cause of cancer related death in females involving a variety of histological diagnosis. It accounts for 6% of all cancers. Though it is one of the treatable cancers due to its sensitivity to anticancer therapies, it frequently does not result in symptoms until the cancer has spread extensively. Objectives: To study the incidence, histopathological spectrum and clinical correlates of ovarian tumours at B.P. Koirala Institute of Health Sciences (BPKIHS). Methods: A cross-sectional study was undertaken during a period of one year (1st Jan. 31st Dec 2006). The tumors were classified according to WHO classification after thorough examination of H&E slides under light microscope. Data on clinical presentation and physical findings were also recorded in each case. Results: There were a total of 83 cases. Surface epithelial tumors emerged as the commonest variety accounting for 47%, followed by Germ cell tumors (45.8%). Sex . cord stromal tumors and metastatic tumors accounted 3.6% each. The age range was 10 . 86 years. Metastatic tumors involved younger age groups. Abdominal mass was the commonest clinical presentation followed by pain abdomen. Conclusion: At BPKIHS, ovarian tumors were found to occur in wide range of age (10-86years) with abdominal mass and pain abdomen being the commonest mode of clinical presentation .Histology revealed that surface epithelial tumors and germ cell tumors together constitute the large majority of the case (92.8%). An accurate histological diagnosis and staging is therapeutically and prognostically important. DOI: http://dx.doi.org/10.3126/hren.v10i2.6570 Health Renaissance 2012; Vol 10 (No.2); 87-97